The extent to which the introduction of information communication technology is being embraced by the elderly teachers and school administrators in rural secondary schools: a case study of Gokwe south district - Muchochomi, Jennifer Addlight (Midlands State University, 2017)
The purpose of this study was to establish the extent to which Information Communication Technology (ICT) is being embraced by the elderly teachers and school administrators in rural secondary schools in Gokwe South District. The review of literature indicated that central to the embracing of ICT in rural secondary schools are aspects such as, ICT literacy among teachers and administrators, attitude of the elderly teachers, infrastructural developments and community involvement. Descriptive survey design was used for the study. Research instruments used for data gathering included questionnaires for teachers and heads of departments, interview guide for heads and school pupils as well as observations and document analysis guide. Quantitative data obtained was summarised using descriptive statistics such as mean, standard deviation frequencies and percentages and was presented in form of tables, charts and graphs and also in narrative form. The findings of the study revealed that basic ICT hardware and software are available in most schools but they are not adequate for both administration as well teaching and learning. Even though administrators are provided with computers and seem willing to fully embrace ICT in school administration, inadequacy of hardware and relevant software is their greatest impediment. The findings indicated that teachers are showing positive steps towards embracing ICT but the lack of resources remains a challenge, as well as lack of training on how to use the computers and other ICT facilities. The researcher recommended that schools should engage in in-service teacher training programmes for elderly teachers who were never trained in ICT use. Also school heads should allow teachers and pupils to use the available resources rather than locking them up in store rooms. The government should also subsidize ICT tools for educational purposes so that schools can acquire them affordably.